2001
DOI: 10.1007/s002770100329
|View full text |Cite
|
Sign up to set email alerts
|

The von Willebrand factor collagen-binding activity assay: clinical application

Abstract: A collagen type III based collagen-binding assay was developed for measuring the functional activity of the von Willebrand factor. The assay had a low coefficient of variance (4.8%) for normal values under optimized conditions. The results of the collagen-binding activity (CBA) assay correlated with ristocetin cofactor activity tested in normal plasma samples (n=29). We found that the CBA of blood group O is lower than that of other blood groups. The test was used for the diagnosis of von Willebrand's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Measurement of VWF:CB is a very sensitive test to detect the freshly secreted VWF due to the content of high molecular weight multimers. Thus, as response to AVP, the increase in VWF:CB is higher than the increase in VWF:Ag reflecting this selective release of very high molecular weight multimers with greater functionality and thus greater capacity to bind to collagen [24]. Our VWF:CB assay uses Collagen type I, so that this assay is even more precise to measure VWF:activity and to detect VWF high molecular weight multimers than other VWF:activity tests [17].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of VWF:CB is a very sensitive test to detect the freshly secreted VWF due to the content of high molecular weight multimers. Thus, as response to AVP, the increase in VWF:CB is higher than the increase in VWF:Ag reflecting this selective release of very high molecular weight multimers with greater functionality and thus greater capacity to bind to collagen [24]. Our VWF:CB assay uses Collagen type I, so that this assay is even more precise to measure VWF:activity and to detect VWF high molecular weight multimers than other VWF:activity tests [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another study utilizing the VWF:CB to help characterize VWF concentrates was performed by Lethagen et al 105 VWF:RCo and VWF:CB correlated with each other, but not with VWF:Ag, and there were substantial differences noted between the six concentrates assessed. Yet more studies performed on VWF-cleaving protease (ADAMTS13) measured by residual VWF:CB activity by Gao et al 106,107 The authors concluded that measurement of the VWF-cleaving protease activity using residual VWF:CB activity was a simple and rapid method for diagnosing TTP, and that the VWF-cleaving protease activity in patients with TTP was markedly lower than those of patients with tumors. The VWF:CB continued to make inroads into transfusion practice when Burnouf et al used the VWF:CB to help assess the content and functional activity of VWF in apheresis plasma.…”
Section: Early History-the 1990smentioning
confidence: 99%